2005
DOI: 10.1086/426006
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Evolution of Clumpy Tidal Tails around Globular Clusters

Abstract: We present some results of numerical simulations of a globular cluster orbiting in the central region of a triaxial galaxy on a set of ''loop'' orbits. Tails start forming after about a quarter of the globular cluster orbital period and develop, in most cases, along the cluster orbit, showing clumpy substructures as observed, for example, in Palomar 5. If completely detectable, clumps can contain about 7000 M each, i.e., about 10% of the cluster mass at that epoch. The morphology of tails and clumps and the ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
58
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 43 publications
15
58
1
Order By: Relevance
“…3, one can also clearly see the so-called "tidal tail clumps" (star density enhancements) at about 150 pc from the cluster centre. These clumps were mentioned probably for the first time in Capuzzo Dolcetta et al (2005) and discussed in more detail by Küpper et al (2008). We observe these clumps in all our models (see the model videos at the FTP link shown in the footnote to page 809).…”
Section: Shape Parameters Of the Cluster Modelssupporting
confidence: 63%
“…3, one can also clearly see the so-called "tidal tail clumps" (star density enhancements) at about 150 pc from the cluster centre. These clumps were mentioned probably for the first time in Capuzzo Dolcetta et al (2005) and discussed in more detail by Küpper et al (2008). We observe these clumps in all our models (see the model videos at the FTP link shown in the footnote to page 809).…”
Section: Shape Parameters Of the Cluster Modelssupporting
confidence: 63%
“…Leon et al 2000). Similar clumps were found by Capuzzo Dolcetta et al (2005) in N -body simulations of clusters on eccentric orbits. More recently, Küpper et al (2008) and carried out detailed studies of the orbits of escaping stars and showed that overdensities along the tails are expected even for clusters on circular orbits.…”
Section: (A) Mass Loss and Cluster Dissolutionsupporting
confidence: 86%
“…Star density distortions, elongation and tidal tails are expected to be detected also in the radial density profile (see for example Odenkirchen et al 2003;Capuzzo-Dolcetta et al 2005). Therefore as a second step of our analysis, we studied the projected density profile of NGC 6791.…”
Section: Star Density and Surface Brightness Profilesmentioning
confidence: 99%